Group Supervision for Counsellors-in-Training - Westwood, Marvin J. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper describes the use of the group format to create quality learning conditions for counsellor trainee supervision. The author details how the effective use of group process integrates the individual skills of the supervisor, while building upon the existing skills of other group members. The advantages of this approach are individually presented and discussed. Following the presentation of a rationale for group supervision, the paper concludes with some recommendations on how supervisors can design and effectively lead such a group.